The etiology of mental disorders: public endorsement of traditional Chinese beliefs in Macau - Found, Andrew; Duarte, Carlos (The International Journal of Social Psychiatry, 2013)
BACKGROUND: Public beliefs concerning the causes of mental disorders are important in their effective treatment. The relative importance of public beliefs related to the etiology of mental disorders among Chinese populations and their relationship to other attitudes to mental disorders are poorly understood. AIMS: To investigate the endorsement of beliefs related to the etiology of mental disorders in Macau, in particular, traditional Chinese beliefs, and to explore their relationship to general attitudes towards mental disorders. METHODS: A survey of 361 members of the public measured attitudes towards 32 possible causes of mental disorders as well as contact with and social distance from individuals with a mental disorder. RESULTS: The results indicated that traditional Chinese beliefs were ranked with relatively low importance compared with psychosocial causes. Traditional beliefs related to two underlying factors and were significantly higher in participants with lower education levels. There was a significant negative correlation between endorsement of traditional beliefs and contact with individuals with a mental disorder and a significant positive correlation between endorsement of traditional beliefs and desired social distance from individuals with a mental disorder. CONCLUSION: Factors underlying traditional Chinese beliefs concerning the causes of mental disorders are associated with more negative attitudes towards individuals with a mental disorder, with such beliefs more strongly endorsed by those with relatively lower education levels.
Keywords: Adolescent; Adult; Aged; Attitude to Health; Chinese; Female; Health Knowledge; Attitudes; Practice; Humans; Macau; Male; Medicine; Chinese Traditional; Mental Disorders; Mental disorder; Middle Aged; Surveys and Questionnaires; Young Adult; etiology; lay theories

Gender, sibling position and parental expectations: A study of Chinese college students - Found, Andrew; Sam, David (Journal of Family Studies, 2013)
Differences in parental expectations related to cultural background, gender and sibling position were investigated among Chinese college students in Macau. Three-hundred and forty-four Chinese college students completed a questionnaire which included measures of parental expectations and psychological distress, as well as information about their gender, cultural background (Mainland China or Macau) and sibling position. Participants born in mainland China reported significantly higher perceived parental expectations (PPE) compared with students from Macau. Contrary to predictions, there was no evidence of a difference in PPE in relation to gender or being the first-born sibling. These findings are discussed in terms of changes in family values and parental attitudes within Chinese society over the past few decades.
Publisher: Routledge _eprint: https://doi.org/10.5172/jfs.2013.19.3.285
Keywords: Chinese; gender; parenting; siblings; students